2006
DOI: 10.1159/000096108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calcium on the Erosive Potential of Acidic Candies in Saliva

Abstract: Theoretical calculations have shown that acidic candies may be potentially erosive upon consumption. However, little is known about the protective effect of adding calcium to potentially erosive candies and about the protective effects of saliva that cannot be fully accounted for by theoretical calculations. Therefore, the aims of this study were to (1) determine the erosive potential of acidic candies with and without calcium and (2) to determine differences between theoretically calculated erosive potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
7

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 45 publications
3
23
0
7
Order By: Relevance
“…A recent study showed that the consumption of acid candies with calcium resulted in lower critical pH and significantly less erosive potential than acid candies without calcium [26]. However, the lack of measurement of the content of these ions is a study limitation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the consumption of acid candies with calcium resulted in lower critical pH and significantly less erosive potential than acid candies without calcium [26]. However, the lack of measurement of the content of these ions is a study limitation.…”
Section: Discussionmentioning
confidence: 99%
“…16 Furthermore, an in vitro study has demonstrated that the addition of calcium to acidic candies results in a reduction of their capacity to bring about dental erosion. 17 Such additions, especially in the form of consumer self-modifi cation with other edible products, are unlikely to raise regulatory obstacles.…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with comparable studies showing the erosive potential of solid acidic candies. [21][22][23][24][25] The smallest decrease in salivary pH in vivo was observed after administration of a single dose of 'Magic spray strawberry' . This is probably related to three factors.…”
Section: Discussionmentioning
confidence: 99%